Japanese imports of Brazilian raw cotton in the second half of the 1930s: the beginning of significant Japanese-Brazilian trade and investment relations - Delanghe, Henri (História Econômica & História de Empresas, 2012)
The kind of evidences offered in this paper to support the argument is in the first place quantitative. Sections one and two provide simple quantitative overviews of Japan's foreign trade in 1928 and 1934. The other sections are more qualitative. A third section, for instance, explains the reality behind the 1934 foreign trade figures. It shows that, in 1934, Japan was a country under tremendous export pressure. A following section explains which strategies Japan adopted to deal with this export pressure. A final section explains how Brazil fitted into this strategic framework. It must be emphasized that this paper is on how trade with Brazil met Japanese foreign trade objectives. It is not about how trade with Japan met Brazilian foreign trade objectives. This paper also does not provide details on Brazil's growth as a producer of raw cotton. This is already a well documented historical reality.